Influence on organizational climate survey and organizational commitment case in Jakarta / Syukurriah Idrus and Prof. Dr. Fauziah Noordin - Idrus, Syukurriah; Noordin, Fauziah (2012)
ABC Group had never conducted any organizational climate survey in the company ever since it was incorporated in 1989 while XYZ Group since 2003. Therefore, it is difficult for the management to make any decision regarding their employees' welfare, as they tend to rely only on their instinct and perception. With the rapid changes in business environment there are challenges occurring that requires company to adapt to the changes while maintaining their productions and retaining their employees. There are more opportunities available in the market today for trained employees. As a result, many employees tend to take advantage on ABC Company and XYZ Company in term of using the companies as a stepping-stone for their career development. This is because ABC Company and XYZ Company do not really know the real employees' expectation towards the company regarding their organizational commitment level.